Emerging technologies for advancing microalgal photosynthesis and metabolism toward sustainable production - Hu, Jingyan; Meng, Weizhao; Su, Yixi; Qian, Cheng; Fu, Weiqi (Frontiers in Marine Science, 2023)
Microalgae are unicellular photosynthetic microorganisms that play a vital role in primary production and have diverse applications in various industries. They have high photosynthetic and metabolic capacities and can produce a variety of valuable metabolites, such as lipids, carbohydrates, pigments, and proteins. However, practical applications of microalgae are limited to high-value products due to the high production costs. Algal biotechnology faces challenges such as low energy utilization efficiency and product yield that are currently inadequate to fulfill commercial production. To overcome these challenges, emerging technologies have shown promise to achieve higher production efficiency, including molecular manipulation of photosynthetic efficiency and metabolic activities. Here, we provided an overview of the importance, diversity, and photosynthesis of microalgae, as well as strategies for enhancing their photosynthetic efficiency. We discussed various approaches for improving microalgal photosynthesis, including strain selection and optimization, rational genetic modification, and innovative technologies such as spectral recomposition of light, nanomaterials, advanced cultivation systems, and symbiotic systems. Additionally, we summarized metabolic engineering strategies that focus on optimizing the synthesis of value-added metabolites, such as pigments, long-chain polyunsaturated fatty acids, starch, proteins, and hydrogen in microalgae. By concentrating on improving photosynthetic efficiency and the synthesis of bioactive metabolites, this review provided valuable insights into enhancing microalgae production yields. Overcoming limitations in microalgae production costs can lead to broader applications in various industries. Furthermore, we highlight the potential of these strategies in increasing the efficiency of microalgae as a sustainable source for high-value products.